1D monodirectional or 2D quasi-uniaxial parallel heat fluxes: A discussion on 'Soil thermal conductivity estimated using a semi-analytical approach'. (February 2022) - Chu, Zhaoxiang
Abstract: This letter is a comment to the published paper entitled, ''Soil thermal conductivity estimated using a semi-analytical approach" (by Rubin and Ho, Geothermics, 2021, 92: 102051). In the reviewed article, an enhanced semi-analytical model was proposed to evaluate the effective thermal conductivity of three-phase (solid-liquid-gas) soils by changing the assumption of 1D monodirectional to 2D quasi-uniaxial parallel heat fluxes in pore-scale soil heat conduction process. The significant innovation, some shortcomings and further research directions were discussed in this comment. In addition, some statements, conclusions and misprints occurred in the published version were also mentioned, indicating that more careful proof, necessary corrigendum and some supplementary materials are required to avoid confused presentation and improve the reliability.